Influence of Government Policy on Highland Agriculture Development in Enrekang Regency, South Sulawesi, Indonesia - Idris Summase; M. Saleh S. Ali; Darmawan Salman; Didi Rukmana (International Journal of Agriculture System, 2019)
Upland agriculture faces threats in the ecological crisis that will affect the sustainability of highland communities. The process lasts quite long because of external and internal influences, leading to ecological exploitation. Agricultural development, is closely related to the influence of government policy. Research focuses on discussing aspects of policy influence on the development of upland agriculture. The research is a qualitative study, using an inductive approach, the case of ethnic thorn communities in Enrekang Regency. The results of the study indicate that the three main policies that influence the development of upland agriculture are: 1). Political policy and government system, 2). Rural development policies and infrastructure, 3). Decentralization or regional autonomy, 4). Economic policies, especially investment and markets. The conclusion is that the development of agriculture is economically progressing in the shadow of the ecological crisis, drought, flooding and impact on humanitarian crisis, because it needs arrangements in land management and the application of technology for agricultural development.